2019
DOI: 10.3390/ma12244244
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Polymer Powder on the Properties of a Cold-Recycled Mixture with Foamed Bitumen

Abstract: The paper investigates the influence of redispersible polymer powder (RPP) on the physical and mechanical properties of a cold-recycled mixture with foamed bitumen (CRM-FB). Four types of RPP with a varied chemical base were used: VA-VeoVA, VA-VeoVa-Ac, EVA and VA/VV/E/Ac. The polymer powder-modified cold recycled mixture with foamed bitumen, (P)CRM-FB, was composed of 45.8% reclaimed asphalt pavement (RAP), 45.8% natural aggregate (VA), 3.0% Portland cement CEM I 42,5R, 3.0% foamed bitumen 50/70 and 3.0% RPP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Examples of the powder microstructure are shown in Figure 1 , whereas the chemical composition of the polymer powder is shown in Table 3 . Detailed information on the polymer powder used in this study can be found elsewhere [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Examples of the powder microstructure are shown in Figure 1 , whereas the chemical composition of the polymer powder is shown in Table 3 . Detailed information on the polymer powder used in this study can be found elsewhere [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bituminous binders reduce the stiffness of the mixture while maintaining proper cohesion and increased deformability. However, preliminary research results [ 26 ] show that the polymer powder used in cement- and foamed bitumen-bound mixtures provides high cohesion without increasing the stiffness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Permanent deformation generated in the foundation or mineral base layers is the distress that requires extensive maintenance. One of the techniques recommended for eliminating the cause of permanent deformation is the environmentally friendly deep-cold recycling technology (CR) [ 1 , 2 , 3 , 4 ]. Pavement lower layers produced using CR are semi-rigid base courses that are typically made with bituminous binders (such as emulsion or foamed bitumen) and mineral binders (Portland cement, hydrated lime, fly ash, or cementitious dusts) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%